May phytophenolics alleviate aflatoxins-induced health challenges? A holistic insight on current landscape and future prospects - Rasouli, Hassan; Nayeri, Fatemeh Dehghan; Khodarahmi, Reza (Frontiers in Nutrition, 2022)
The emergence of aflatoxins (AFs) raised serious global concerns about world food safety. AFs are lethal carcinogenic mycotoxins, causing damage to the liver, kidney, and gastrointestinal organs. Long-term exposure to chronic concentrations of AFs is shown to lead to the development of cancer. Almost a variety of food commodities, crops, spices, nuts, and processed foods are at risk of AFs contaminants. Herein, we first reviewed factors influencing the occurrence of AFs, frequency of AF-based academic investigations, world distribution of AFs, and the association between AFs and pathogenesis of human chronic diseases. Next, the current trends in the application of polyphenols (PPs) to alleviate AFs toxicity profile are discussed. According to our results, PPs are promising natural candidates to help detoxification of AFs in complex ways. Accordingly, PPs could decrease AFs-associated oxidative stress and genotoxic, mutagenic, and carcinogenic effects through improving cellular antioxidant balance, regulation of signaling pathways, and modification of gene expression profile. We also found that the occurrence of AFs varies from site to site, and global policies on AFs prevention cannot equally be considered for all countries. Overall, our results demonstrated that considering PPs in antioxidant therapies to alleviate complications of AFs requires improvement in their bioavailability, pharmacokinetics, tissue clearance, and off-target mode of action. Due to the emergencies in the elimination of AFs in foodstuffs, further large-scale clinical assessment of PPs to decrease the toxicity of AFs in the human body is highly required.